General test methods; forensic psychophysiology; forensic sciences; terminology; conformity assessment; statistical methods; forensic engineering - International, ASTM. ([S.l.] : ASTM International, 2009)
Covers: Conformity Assessment; Forensi Sciences; Frensic Psychophysiology; Hazard Potential of Chemicals; Particle and Sprey Characterization; Quality and Statistics; Thermal Measurements; and Nanotechnology.